Evaluation of Solid Medical Waste Treatment Implementation Using Sterilwave Technology at the Health and Environmental Laboratory Unit of the Riau Provincial Health Office - Marwad; Oktavia Dewi; Sangap Daniel Tarigan (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2026)
Solid medical waste management is a critical aspect of environmental health that requires proper handling to prevent environmental contamination and protect public health. The Environmental Health Laboratory Unit (UPT Labkesling) of Riau Province has implemented Sterilwave technology, a modern microwave-based waste treatment system, as an alternative to conventional incineration. However, the implementation still faces several operational challenges. This study aims to evaluate the implementation of solid medical waste treatment using Sterilwave technology and identify factors affecting its effectiveness. The research employed a qualitative approach with a case study design and problem-solving cycle method. Data collection was conducted through observation, in-depth interviews, and documentation during October 2025. Analysis used fishbone diagrams and the USG (Urgency, Seriousness, Growth) method to determine problem priorities. The study identified five main problems, with priority given to the suboptimal process of solid medical waste treatment using Sterilwave. Fishbone analysis revealed that problem causes originated from six factors: human resources, methods, materials, machines, funds, and environment. The recommended solution is a combination of soft approaches (capacity building through training and supervision) and hard approaches (provision of supporting facilities such as calibration systems, stabilizers, and mechanical ventilation). This strategy is considered effective and efficient because it can be implemented with existing resources without major investment and has potential for long-term sustainability in maintaining treatment effectiveness and safety.